Organizational generativity the appreciative inquiry summit and a scholarship of transformation - Cooperrider, David L. (Advances in appreciative inquiry ;, 2013)
Appreciative Inquiry has touched and inspired the work of thousands who apply its development principles in a wide range of settings including industry, government, spiritual and not-for-profit organizations. The Advances in Appreciative Inquiry series facilitates an emergent dialogue within the social sciences and supports innovative and challenging scholarly work. It is dedicated to the advancement of Appreciative Inquiry as an approach to organizational and human development, and as an interdisciplinary, non-deficit theory of positive change processes in human systems. Guided by the ethos of Appreciative Inquiry, the book series supports an ongoing, distributed inquiry into the true, the good, the better and the possible. It is dedicated to advancing a "scholarship of the positive" and "positive scholarship." This volume aims to push the frontiers and solicit new tools and insights for expanding the state-of-the-art applications of Appreciative Inquiry. It revolves around three fundamental aspects of organizational generativity, namely: generative knowledge and organizational life, collective action and the appreciative inquiry summit, and sustainable inter-generative dynamics.